2023
DOI: 10.2196/44161
|View full text |Cite
|
Sign up to set email alerts
|

Smart Glasses for Supporting Distributed Care Work: Systematic Review

Abstract: Background Over the past 2 decades, various desktop and mobile telemedicine systems have been developed to support communication and care coordination among distributed medical teams. However, in the hands-busy care environment, such technologies could become cumbersome because they require medical professionals to manually operate them. Smart glasses have been gaining momentum because of their advantages in enabling hands-free operation and see-what-I-see video-based consultation. Previous researc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
(456 reference statements)
1
11
0
Order By: Relevance
“…Prior studies examining this issue have made the same conclusion and suggest that degree of variability and multitasking in EMS teams necessitates novel interventions to support EMS providers (Chisholm 2000). For example, hands-free, semi-automated wearable technology such as smart glasses can be adopted to better support EMS workflow (Zhang 2021a(Zhang , 2021b(Zhang , 2022. Other studies demonstrate that interventions to improve teamwork11 or integrate health information technology (HIT) (Zhang 2020) can improve EMS care.…”
Section: Discussionmentioning
confidence: 92%
“…Prior studies examining this issue have made the same conclusion and suggest that degree of variability and multitasking in EMS teams necessitates novel interventions to support EMS providers (Chisholm 2000). For example, hands-free, semi-automated wearable technology such as smart glasses can be adopted to better support EMS workflow (Zhang 2021a(Zhang , 2021b(Zhang , 2022. Other studies demonstrate that interventions to improve teamwork11 or integrate health information technology (HIT) (Zhang 2020) can improve EMS care.…”
Section: Discussionmentioning
confidence: 92%
“…It also serves as a platform for visualization of educational videos such as open surgical procedures that are live streamed to encourage medical students and residents from public health centers to use the telemedicine features on their own smartphones and tablets as an educational tool. To aid online video streaming surgery observation, tiny computers called smart glasses that have an internet connection and a head-mounted monitor and video camera are used to watch professional surgeons perform surgeries in order to learn new techniques and advance existing ones [32].…”
Section: Videos In Telemedicinementioning
confidence: 99%
“…Currently, the major employer of WA XROs, WA Country Health Service (WACHS), arranges radiographers from larger clinical (expert) centers to provide telephone support to their XROs practicing in smaller rural/remote centers to address these issues and as a means for the XROs' CPD. Although the telephone support is common for traditional telehealth practice [2], our previous qualitative study on WA XROs' competence, and barriers and facilitators to their radiography practice published in 2020 identified that videoconferencing (VC) support appears to be a better approach [1]. This kind of VC support for XROs was proved effective for improving quality of X-ray images produced by XROs in another Australian state (Queensland) in 2017 [3].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of VC support for XROs was proved effective for improving quality of X-ray images produced by XROs in another Australian state (Queensland) in 2017 [3]. However, the major issues with the traditional VC platform such as the one used in the Queensland's XROs study [3] are a limited field of view of the fixed camera for the experts (supervising radiographers) to understand clinical situations faced by their XROs and the requirement of hand control for operating the VC equipment [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation